Bone Mineral Density and Osteoporosis after Preterm Birth: The Role of Early Life Factors and Nutrition - Claire L. Wood; Alexander M. Wood; Caroline Harker; Nicholas D. Embleton (International Journal of Endocrinology)
The effects of preterm birth and perinatal events on bone health in later life remain largely unknown. Bone mineral density (BMD) and osteoporosis risk may be programmed by early life factors. We summarise the existing literature relating to the effects of prematurity on adult BMD and the Developmental Origins of Health and Disease hypothesis and programming of bone growth. Metabolic bone disease of prematurity and the influence of epigenetics on bone metabolism are discussed and current evidence regarding the effects of breastfeeding and aluminium exposure on bone metabolism is summarised. This review highlights the need for further research into modifiable early life factors and their effect on long-term bone health after preterm birth.